THE ROLE OF THE GEOGRAPHIC INFORMATION SYSTEMS IN THE WATER SUPPLY SYSTEMS (Journal of Universal Science Research, 2023)
Geographic Information Systems (GIS) have become indispensable tools in modern water resource management. This article explores the pivotal role of GIS in optimizing water supply systems, discussing its ability to map infrastructure, monitor resources, and facilitate informed decision-making for sustainable water management.